The effectiveness of physical activity in cardiorehabilitation - M. Yu. Yakovlev; O. D. Lebedeva; V. E. Vladimirsky; E. V. Vladimirsky; A. N. Lunina (National Electronic Information Consortium (NEICON), 2022)
The review shows that the molecular mechanisms initiated by physical exertion underlie the multifactorial influence of the latter on the function of the cardiovascular system and the course of cardiac diseases. Exercise is an important component of the therapeutic treatment in patients with cardiovascular diseases, which is confirmed by the results of a metaanalysis that included 63 studies that were associated with various forms of aerobic exercise of different intensity (from 50 to 95 % VO2) for 1 to 47 months, which showed that exercise-based CR improves cardiovascular function. Knowledge of the molecular basis of the impact of physical activity makes it possible to use biochemical markers to assess the effectiveness of rehabilitation programs.